Knowledge, Attitude, and Practices of Araling Panlipunan Teachers Towards Reflective Approach: An Input for Learning Action Cell - Ephraim D, Clemen John; Hernando Jr. L., Bernal (RIRAI Publisher, 2025)
As online, blended, and face-to-face instruction modalities are getting more popular, reflective approaches to instruction could improve learning outcomes in the Philippines. This shift demands that educational approaches be critically reevaluated. Enhancing the quality of instruction in the Araling Panlipunan subject requires an understanding of teachers' reflective approach-related knowledge, attitudes, and practices (KAP). Offering insights into current use in the Philippine educational setting, this study examines the KAP of Araling Panlipunan teachers toward reflective teaching. Using a sequential mixed-methods research design, the study first collected quantitative data via questionnaires, then collected qualitative data from 50 teacher respondents through semi-structured interviews. The results show a